2010
DOI: 10.1007/s11803-010-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based methodology for assessing seismic vulnerability and capacity of buildings

Abstract: This paper presents a performance-based methodology for the assessment of seismic vulnerability and capacity of buildings. The vulnerability assessment methodology is based on the HAZUS methodology and the improved capacitydemand-diagram method. The spectral displacement (S d ) of performance points on a capacity curve is used to estimate the damage level of a building. The relationship between S d and peak ground acceleration (PGA) is established, and then a new vulnerability function is expressed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The first one is the probabilistic seismic hazard analysis. For instance, the 2001 seismic ground motion parameters zonation (SGMPZ) map (national standard: GB18306-2001) (Hu et al 2001, Gao 2003 was based on this method and has been widely used in assessing the seismic vulnerability and capacity of buildings in China (Shibin et al 2010, Xu et al 2011. Another method is the neo-deterministic seismic hazard analysis (NDSHA, Wang 2010, Peresan and Nekrasova 2014), which has been adopted to estimate the seismic hazard in some regions, such as Italy (Zuccolo et al 2010), the Longmenshan fault zone, the origin of the 2008 Wenchuan earthquake (Yong and Booth 2011), and the Beijing-Tianjin-Tangshan area (Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the probabilistic seismic hazard analysis. For instance, the 2001 seismic ground motion parameters zonation (SGMPZ) map (national standard: GB18306-2001) (Hu et al 2001, Gao 2003 was based on this method and has been widely used in assessing the seismic vulnerability and capacity of buildings in China (Shibin et al 2010, Xu et al 2011. Another method is the neo-deterministic seismic hazard analysis (NDSHA, Wang 2010, Peresan and Nekrasova 2014), which has been adopted to estimate the seismic hazard in some regions, such as Italy (Zuccolo et al 2010), the Longmenshan fault zone, the origin of the 2008 Wenchuan earthquake (Yong and Booth 2011), and the Beijing-Tianjin-Tangshan area (Xie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the seismic risk studies usually give as outputs seismic hazard maps in PGA or Sa, while other IM such as Sd cannot be applied without an intermediate step, the calculation of the performance point, which hinders their comparison. The regulation in force in Costa Rica (Colegio Federado de Ingenieros y de Arquitectos (CFIA), 2011, 2018) and the performance point identification method (Shibin et al, 2010) have been employed for the conversion of the IM.…”
Section: Application To Costa Rica: Results and Discussionmentioning
confidence: 99%
“…As summarized in Supplementary Table S4, the years built for the investigated buildings in the downtown area of Taiyuan are mainly in the ranges of 1977-1989, 1990-2000, and 2001-2014. To differentiate the vulnerability of buildings built in accordance with different versions of seismic design codes, we digitalized the second, third and fourth zonation maps issued in 1977, 1990 and 2001 by the China Earthquake Administration for our case study area, as shown in Extended Data Figure 5(a)-(c). Combining the dominant built year range with seismic design code information, the vulnerability levels (precode, low-code, moderate-code, high-code) of different building types in the case study area can be determined (as listed in Supplementary Table S5) according to the judgement criteria modified after Table 5 in Lin et al 63 . The building vulnerability curve (which describes the relationship between the ground shaking indicator and loss ratio; loss ratio refers to the ratio between the structure repairment cost and structure replacement cost) is generated by combining the building fragility curve and the consequence function.…”
Section: Vulnerability Curves For Different Building Typesmentioning
confidence: 99%
“…Loss ratios (%) in different damage states for steel-RC and masonry buildings with simple decoration63 .Notably, for the damage state "Basically intact", the loss ratio is uniformly set as 0 before deriving the vulnerability curves in Extended Data Figure5(d)-(f).…”
mentioning
confidence: 99%